2015
DOI: 10.24198/jkp.v1i1.51
|View full text |Cite
|
Sign up to set email alerts
|

Efek Spiritual Emotional Freedom Techniqueterhadap Cemas dan Depresi, Sindrom Koroner Akut

Abstract: Sindrom koroner akut (SKA) merupakan penyakit jantung penyebab kematian. Gejala depresi, kecemasan, dan stres meningkat pada pasien SKA. Gejala ini dapat memengaruhi proses pengobatan dan penyembuhan serta menimbulkan komplikasi. Penelitian ini bertujuan untuk mengidentifikasi pengaruh SEFT terhadap penurunan gejala depresi, kecemasan, dan stres pada pasien SKA yang dirawat di ruang rawat intensif jantung. Rancangan penelitian menggunakan quasi eksperimen, teknik pengambilan sampel dengan consecutive sampling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
5
0
4
Order By: Relevance
“…This research is in accordance with the results of the study. Bakara et al (2013) Seft interventions can significantly lower levels of depression, anxiety and stress in SKA (Acute Coronary Syndrome) patients. According to the researchers' assumptions, there is a significant influence between Spiritual Emotional Freedom Technique (SEFT) therapy on the decrease in anxiety levels because SEFT therapy utilizes the body's energy system to improve the state of the human mind, emotions and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This research is in accordance with the results of the study. Bakara et al (2013) Seft interventions can significantly lower levels of depression, anxiety and stress in SKA (Acute Coronary Syndrome) patients. According to the researchers' assumptions, there is a significant influence between Spiritual Emotional Freedom Technique (SEFT) therapy on the decrease in anxiety levels because SEFT therapy utilizes the body's energy system to improve the state of the human mind, emotions and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The related study that has done there found significant differences between levels of depression, anxiety, and stress before and after SEFT intervention (p <0.05), between the intervention group and the control group (p <0.05). 8 SEFT intervention helps to reduce depression, anxiety, and stress among chronic kidney failure patients. Spiritual is able to build self-confidence, bring calm, relax, and feel the presence of God Almighty, as a result, it can stimulate the hypothalamus for reducing the production of CRF (Corticotrophin Releasing Factor).…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu kecemasan keluarga dapat dikomunikasikan kepada pasien sehingga berakibat memperparah penyakit dan menghambat proses penyembuhan (Stuart & Laraia, 2019). Faktor resiko yang berhubungan dengan kecemasan anggota keluarga diruang perawatan intensif adalah jenis kekerabatan dengan pasien, tingkat pendidikan, tipe perawatan pasien, kondisi medis pasien, pertemuan keluarga dengan perawatan, cara penanggulangan, dan kebutuhan keluarga (Bakara et al, 2015).…”
Section: Pendahuluanunclassified